TEAMWORK AND TRAINING VARIABLES AS PREDICTORS OF WORKERS' PERFORMANCE IN PUBLIC ORGANISATIONS IN CROSS RIVER STATE, NIGERIA
There has been persistent poor performance among workers in public organisations in Cross River State of Nigeria over the years. The trend is exacerbated by lack of teamwork and unsystematic training programmes. Previous studies have focused more attention on staff performance appraisal, commitment and job involvement with less attention paid to the combined effects of teamwork (communication, team-spirit, recognition, collaboration) and training (training needs identification, plan, design, delivery, evaluation variables) on workers’ performance. This study, therefore, examined the extent to which teamwork and training variables predicted workers’ performance in public organisations in Cross River State, Nigeria. The descriptive survey design of ex-post facto type was employed. Cluster sampling technique was adopted to divide the public service into Ministries, Departments and Agencies (MDAs). Purposive sampling technique was used to select 10 ministries, 10 departments and five agencies. These MDAs were stratified along three job cadres, namely: 221 junior, 574 senior and 273 managerial. A total of 1,068 respondents were randomly selected to represent the entire population of public servants in Cross River State. Participants were 584 males and 484 females. Teamwork Variables (r = 0.87), Workers’ Training variables (r = 0.78) and Workers’ Performance Rating (r = 0.86) scales were used for data collection. These were complemented with in-depth interview with selected 15 public service workers across the three cadres in MDAs. Data were analysed using descriptive statistics, Pearson product moment correlation and multiple regression at 0.05 level of significance; while the qualitative data were content analysed. Workers’ performance was: managerial (44.90 ± 1.21), senior (44.23 ± 2.42) and junior (43.13 ± 2.22) cadres. Teamwork and training variables had a significant joint prediction of workers’ performance in public service (R2 = .070, F(9, 1068) = 8.794,) and accounted for 7% in its variance. There was a significant joint prediction of teamwork variables on workers’ performance (R2 = .037, F(4, 1068) = 10.306) and accounted for 3.7% in its variance. Training variables had a significant joint prediction of workers’ performance (R2 = .033, F(5, 1065) = 7.258) and accounted for 3.3% of its variance. Communication (β = -.099, t = -2.792), team-spirit (β = .058, t = 1.565), recognition (β = .104, t = 3.228) and collaboration (β = .134, t = 3.726) had relative contributions to workers’ performance. Training needs identification (r = .112), training design (r = .78), training plan (r = .019) and training evaluation (r = .045) had significant positive relationships with workers’ performance, while training delivery did not. Teamwork (communication, team-spirit, recognition, collaboration) and training (training needs identification, plan, design, delivery, evaluation) variables positively influenced workers’ performance in public organisations of Cross River State, Nigeria. Adequate consideration should be given to these variables so as to improve workers’ performance in public organisations. Attention should be given to employees’ personal characteristics in motivating them to higher performance level.